Prayer in the life of a christian (Confluenţe Bibliologice, 2023)
The given article tells about the importance and purpose of prayer in human life. The meaning of the word prayer is specified, the types of prayers are listed and the provisions of the so-called Alphabet of spiritual life that must be respected by every Christian.
Keywords: prayer; Orthodoxy